Discovering the Spirit of Ubuntu Leadership Compassion, Community, and Respect - Ndlovu, Priscilla Mtungwa; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Discovering the Spirit of Ubuntu Leadership introduces a new leadership model which takes into account the history, culture and economic environment of African women leaders to understand, discover, observe and share their personal leadership experiences.
Keywords: Culture -- Study and teaching; Religion; Religion and sociology; Ethnology -- Africa; Business; Management science; Leadership; International business enterprises; Cultural and Media Studies; African Culture; Religious Studies, general; Business and Management, general; Business Strategy/Leadership.; Social Aspects of Religion; International Business; Electronic books